South Africa - Social Assistance Programs and Systems Review - World Bank (Washington, DC : World Bank, 2022)
Despite being an upper middle-income country, South Africa’s high inequality and the long-lasting legacies of apartheid mean that the country is faced with numerous development challenges, many of which are characteristic of countries with much lower incomes. Poverty and inequality remain two of the country’s most pressing concerns. Alongside extreme inequalities, South Africa struggles with high unemployment, low labour market participation rates, and widespread poverty, including pockets of deep deprivation. In this context, social assistance is a critical policy response on the part of government and represents one of the important successes of the post-apartheid era. This report provides a review of the South African social assistance system and consists of three broad thrusts. First, the review provides a sense of the operation of the social assistance system, the types of benefits it provides through its key programmes, and the tools and administrative systems that support its functioning. Second, it reviews the performance of the social assistance system in terms of coverage, targeting, benefit incidence, adequacy, cost-effectiveness, and outcomes. Third, it assesses the extent to which the system is aligned and equipped to address the so-called “triple challenge” of poverty, inequality, and unemployment as shown by data, and reviews its limitations in the design, delivery systems, and institutional coordination at different administrative levels. The core focus of this paper is on social assistance and, specifically, the system of social grants in South Africa.